PENDEKATAN METODE RAPID APPLICATION DEVELOPMENT PADA PEMESANAN PRODUK BERBASIS WEB - Alfredo Christian; Narawata Adhi (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2021)
XYZ Semarang is a company that produces bathroom fixtures made of ceramics such as washbasins, urinate, closets, faucet stops, showers and others. PT. Inax serves large orders for customers, most of the customers of PT. Inax, among others, ceramic shops, developers in various areas of Semarang, Surabaya, Jakarta, Bandung. But the problem faced so far is the limitations in delivering products to consumers, this happens because the number of sales is inadequate so that it cannot reach the desired area, besides that time is also a bad thing in ordering. The author feels the need to create media that can order the products of PT. Inax so that it is more complete and clear without being limited by time and distance. The Web-based Sanitaryware Order Information System was designed using software, namely Macromedia flash player 7, PHP 4.0 and Apache 2.23, web browsing Internet Explorer, Mozilla Firefox, other designs using Data Flow Diagrams (DFD), Entity Relation Diagram (ERD), Normalization and methodology Insights using the System Life Cycle is a methodology in the application of systems to build and use computer-based systems. SLC steps are evaluated in 5 stages, namely planning, analysis, implementation and use. With this system, it is hoped that it will benefit the company and make it easier for consumers to order and be able to see the latest Sanitation products.